Resposta :
Resposta:
Explicação passo a passo:
[tex]a)[/tex]
[tex](-1,1)^{2} =1,21[/tex]
[tex]b)[/tex]
[tex](-1\frac{1}{2}) ^{3} =(-\frac{3}{2}) ^{3} =-\frac{27}{4}[/tex]
[tex]Obs.:...[/tex]
[tex]1\frac{1}{2}=1+\frac{1}{2}=\frac{2}{2}+\frac{1}{2}=\frac{3}{2}[/tex]
[tex]c)[/tex]
[tex](0,3)^{2} =0,09[/tex]
[tex]d)[/tex]
[tex](\frac{1}{10}) ^{3} =\frac{1}{1000}[/tex]
[tex]e)\:Resposta:1[/tex]
[tex]Regra...[/tex]
[tex]a^{0} =1\:para\:a\neq 0[/tex]
[tex]f)[/tex]
[tex](-\frac{1}{2}) ^{4} =\frac{1}{16}[/tex]
__________________________________________________________
[tex](Base\:negativa)^{PAR} =(+)[/tex]
[tex](Base\:negativa)^{IMPAR} =(-)[/tex]